2009
DOI: 10.1021/bi9013775
|View full text |Cite
|
Sign up to set email alerts
|

GPR37 Surface Expression Enhancement via N-Terminal Truncation or Protein−Protein Interactions

Abstract: GPR37, also known as the parkin-associated endothelin-like receptor (Pael-R), is an orphan G protein-coupled receptor (GPCR) that exhibits poor plasma membrane expression when expressed in most cell types. We sought to find ways to enhance GPR37 trafficking to the cell surface in order to facilitate studies of GPR37 functional activity in heterologous cells. In truncation studies, we found that removing the GPR37 N-terminus (NT) dramatically enhanced the receptor's plasma membrane insertion. Further studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 54 publications
4
89
0
1
Order By: Relevance
“…This implies that the cleavage of GPR37 is evolutionarily conserved in a similar manner as has been demonstrated for ET B R (Kozuka et al, 1991;Grantcharova et al, 2002) and the β 1 adrenergic receptor (Hakalahti et al, 2013). Interestingly, one of the studies aiming to enhance GPR37 plasma membrane trafficking demonstrated that the receptor cell surface expression could be increased significantly by N-terminal truncations (Dunham et al, 2009). In this study, an N-terminal FLAG epitope tag was used to detect the full-length and truncated receptors.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This implies that the cleavage of GPR37 is evolutionarily conserved in a similar manner as has been demonstrated for ET B R (Kozuka et al, 1991;Grantcharova et al, 2002) and the β 1 adrenergic receptor (Hakalahti et al, 2013). Interestingly, one of the studies aiming to enhance GPR37 plasma membrane trafficking demonstrated that the receptor cell surface expression could be increased significantly by N-terminal truncations (Dunham et al, 2009). In this study, an N-terminal FLAG epitope tag was used to detect the full-length and truncated receptors.…”
Section: Discussionmentioning
confidence: 53%
“…GPR37 carries a PSD-95, Discs-large, ZO-1-homology (PDZ)-domain-binding motif at its C-terminus that is known to mediate interaction with a few PDZ-domain-containing proteins (Dunham et al, 2009;Dutta et al, 2014). Such interactions are known to alter receptor function and trafficking (Romero et al, 2011), and thus could modify the susceptibility to cleavage.…”
Section: Gpr37 Cleavage Is Mediated By a Metalloproteinasementioning
confidence: 99%
See 1 more Smart Citation
“…Although PICK1 regulates mGluR7 phosphorylation, clustering, and membrane expression, it is not yet clear what role syntenin-1 may play in this regulation (Boudin et al, 2000;Dev et al, 2000;Suh et al, 2008). Nonetheless, syntenin-1 has been demonstrated to enhance the membrane expression of G protein-coupled receptor 37 (endothelin receptor type B-like) (Dunham et al, 2009). In regards to signaling, syntenin-1 interacts with frizzled-7 and promotes c-Jun phosphorylation, CDC42 activation, and PKCa recruitment to the membrane (Luyten et al, 2008).…”
Section: Additional Gpcr-interacting Pdz Proteinsmentioning
confidence: 99%
“…In some 7TMRs, such as the cannabinoid CB1 receptor, a1-adrenergic receptor, and GPR37, published data show that truncation of the N-terminal region increases plasma membrane expression of these receptors (Andersson et al, 2003;Hague et al, 2004;Dunham et al, 2009). The extracellular surface of biogenic amine 7TMRs affects ligand recognition, ligand "escorting" into the binding pocket, and ligand binding kinetics (Wittmann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%